Barriers to inclusion embedded in the Disability Discrimination Act 1992 (Cth). Issue 3 (November 2022) - Dickson, Elizabeth
The Disability Discrimination Act 1992 (Cth) (DDA) prohibits discrimination by schools against students with disability. The DDA and the associated Disability Standards for Education 2005 (Cth) (DSE) also impose a positive obligation on schools to make reasonable adjustment for students with disabilities. The promise of inclusion implicit in these laws, however, has not always been delivered upon, as there are still opportunities for schools to exclude students with disabilities, without breaching the laws. This article provides an overview of relevant provisions of the DDA and DSE, before considering the legal barriers to inclusion which have been constructed by courts through their interpretation of the DDA.